The Suitability of Cross Cultural Models in Predicting Car Interior Design Preferences - syed mohamed, muhammad syafiq; Mohd Tamrin, Shamsul Bahri; Abdul Rahman, Ahmad Rizal (2013)
Car center stack design is an important feature in a car interior as drivers will interact with car center stacks while using their vehicles. Drivers with different cultural backgrounds may have different expectations of how car center stack designs are supposed to be. Cross cultural models from Hofstede and Hall were utilized to determine the suitability in predicting design preferences.The interpretations of Hofstede’s model from previous researchers were utilized in this study. The interpretations offered by Jhangiani and Marcus on Hofstede’s cultural dimensions did not match with the results showed by this study. Jhangiani and Marcus predicted that high power distance cultures prefers limited choices on interfaces but the results showed otherwise (92% prefers variety of features). It was also inferred from Jhangiani and Marcus that low uncertainty avoidant cultures such as Malaysia would tolerate inefficiency in interface layout and unclear menu labeling, but the results showed the opposite. Future research should consider alternative approaches when it comes to cross cultural design of car center stacks.